Using continuous sedation until death for cancer patients: A qualitative interview study of physicians' and nurses' practice in three European countries. (January 2015) - Seymour, Jane; Rietjens, Judith; Bruinsma, Sophie; Deliens, Luc; Sterckx, Sigrid; Mortier, Freddy; Brown, Jayne; Mathers, Nigel; van der Heide, Agnes; ,
Background: Extensive debate surrounds the practice of continuous sedation until death to control refractory symptoms in terminal cancer care. We examined reported practice of United Kingdom, Belgian and Dutch physicians and nurses. Methods: Qualitative case studies using interviews. Setting: Hospitals, the domestic home and hospices or palliative care units. Participants: In all, 57 Physicians and 73 nurses involved in the care of 84 cancer patients. Results: UK respondents reported a continuum of practice from the provision of low doses of sedatives to control terminal restlessness to rarely encountered deep sedation. In contrast, Belgian respondents predominantly described the use of deep sedation, emphasizing the importance of responding to the patient's request. Dutch respondents emphasized making an official medical decision informed by the patient's wish and establishing that a refractory symptom was present. Respondents employed rationales that showed different stances towards four key issues: the preservation of consciousness, concerns about the potential hastening of death, whether they perceived continuous sedation until death as an 'alternative' to euthanasia and whether they sought to follow guidelines or frameworks for practice. Conclusion: This qualitative analysis suggests that there is systematic variation in end-of-life care sedation practice and its conceptualization in the United Kingdom, Belgium and the Netherlands.